A study on correlation of anemia with left ventricular hypertrophy in chronic kidney disease patients: a cross sectional study from Southern Rajasthan - Meena, O. P.; Meghwal, Hemlata; Meena, Rajesh; Gurjar, Surendra (International Journal of Advances in Medicine, 2022)
Background: Chronic kidney disease is becoming epidemic of twenty-first century. With increasing burden of diabetes and hypertension, chronic kidney disease is becoming rampant in our country. Adverse outcome of CKD includes kidney failure, complications due to decreased kidney function and cardiovascular disease etc. Increasing morbidity and mortality of coronary artery disease in CKD patients make it necessary to develop further researches in these population. Aim and objectives of current study were to demonstrate the correlation of anemia with left ventricular hypertrophy in a cohort of CKD patients in a tertiary care centre. Methods: This study was done over one year on 100 patients of CKD (stage III to V), aged 15-80 years, who had elevated serum creatinine and reduced glomerular filtration rate, haemoglobin <11 gm/dl with ultrasonographic evidence of renal parenchymal disease grade >2. The patients were assessed based on clinical history and a number of laboratory parameters including blood urea, serum creatinine, calcium, inorganic phosphorus, serum electrolytes, iPTH level, Hb, Hct, glomerular filtration rate and left ventricular mass index. Results: There is a significant relationship between of anemia and left ventricular hypertrophy among chronic kidney disease patients. In our study, it was observed that left ventricle mass (left ventricular mass index) increases with increasing severity of anemia. Conclusions: Anemia is widely prevalent in our CKD patients. Severity of anemia is correlated to left ventricular hypertrophy in these patients. Hence correction of anemia early in these group of patients can halt or prevent cardiovascular morbidity and mortality.